2021
DOI: 10.1186/s40634-021-00418-y
|View full text |Cite
|
Sign up to set email alerts
|

Achieving coronal plane alignment in total knee arthroplasty through modified preoperative planning based on long-leg radiographs: a prospective study

Abstract: Purpose This prospective study was undertaken to examine whether the desired coronal plane alignment of limb and prosthetic components in total knee arthroplasty (TKA) could be achieved precisely using conventional jig-based methods by modifying the preoperative planning of bone resection utilizing long-leg radiographs (LLRs). Methods The study included consecutive 245 TKA procedures. Pre- and postoperative radiological variables, i.e., the mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Any deviation from the correct implant alignment can change the knee kinematics and impact patient satisfaction and overall material survivorship [35]. The implant positioning basically depends on the preoperative plan and the surgeons’ surgical skills [18, 35]. In our study, all radiology signs examined were similar across the groups, which means that the implant positioning was not a confounding factor for the reported clinical outcomes.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Any deviation from the correct implant alignment can change the knee kinematics and impact patient satisfaction and overall material survivorship [35]. The implant positioning basically depends on the preoperative plan and the surgeons’ surgical skills [18, 35]. In our study, all radiology signs examined were similar across the groups, which means that the implant positioning was not a confounding factor for the reported clinical outcomes.…”
Section: Discussionmentioning
confidence: 65%
“…Radiographic markers are paramount for assessing a TKA. Any deviation from the correct implant alignment can change the knee kinematics and impact patient satisfaction and overall material survivorship [35]. The implant positioning basically depends on the preoperative plan and the surgeons’ surgical skills [18, 35].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, failure to restore the neutral mechanical axis leads to unfavorable clinical outcomes and prosthesis failure. However, several studies have reported a considerable proportion of outliers exceeding 3° from the neutral mechanical axis in c-TKA [ 12 , 28 , 29 ]. For the distal femoral cutting procedure, the system of IM referencing has generally been adopted in c-TKA, which could be influenced by the individual anatomic factors of the femur [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, failure to restore the neutral mechanical axis leads to unfavorable clinical outcomes and prosthesis failure. However, several studies have reported a considerable proportion of outliers exceeding 3° from the neutral mechanical axis in c-TKA [12,23,24]. For the distal femoral cutting procedure, the system of IM referencing has been generally adopted in c-TKA.…”
Section: Discussionmentioning
confidence: 99%